2007
DOI: 10.1177/159101990701300411
|View full text |Cite
|
Sign up to set email alerts
|

Target Embolization of AVMs: Identification of Sites and Results of Treatment

Abstract: Although cure of cerebral arteriovenous malformations (AVMs) is the ideal goal it is often only possible with smaller sized lesions. This is certainly true if surgery or radiotherapy is used as the treatment strategy. Endovascular treatment, however, allows the possibility of partial treatment directed at specific areas of AVM architecture. With this in mind we retrospectively reviewed our cohort of AVMs to establish which morphological areas we had identified as targets and how the treatment of the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 12 publications
2
13
0
1
Order By: Relevance
“…Метод эндоваскулярной эмболизации оказался эффективным в лечении пациентов с АВМ и структурной эпилепсией. Совершенствование технологии внутрисосудистых вмешательств показывает значительное улучшение результатов в отношении сокращения периоперационных осложнений с высокой радикальностью выключения АВМ [19,20,25,27] Нами получены хорошие результаты лечения пациентов с эпилептическим типом течения АВМ головного мозга в отношении контроля над эпилептическими приступами после комбинированной инвазивной терапии. Радикальность выключения АВМ имела статистическую значимость для свободы от приступов: тотальное выключение позволяла обеспечить лучший контроль над приступами в сравнении с парциальной эмболизацией.…”
Section: Discussionunclassified
“…Метод эндоваскулярной эмболизации оказался эффективным в лечении пациентов с АВМ и структурной эпилепсией. Совершенствование технологии внутрисосудистых вмешательств показывает значительное улучшение результатов в отношении сокращения периоперационных осложнений с высокой радикальностью выключения АВМ [19,20,25,27] Нами получены хорошие результаты лечения пациентов с эпилептическим типом течения АВМ головного мозга в отношении контроля над эпилептическими приступами после комбинированной инвазивной терапии. Радикальность выключения АВМ имела статистическую значимость для свободы от приступов: тотальное выключение позволяла обеспечить лучший контроль над приступами в сравнении с парциальной эмболизацией.…”
Section: Discussionunclassified
“…If a high-grade AVM is not considered safe for any type of curative treatment, embolization may serve as a way to decrease rupture risk by treating specific features associated with hemorrhage such as nidal aneurysms or venous ectasia. [ 19 23 25 ] Additionally, embolization may be used for the reduction of AV shunting through the lesion, improving or resolving a neurologic deficit attributable to vascular steal. [ 4 11 20 24 ] The potential benefits of this type of palliative embolization must be weighed against the published evidence of increased hemorrhage risk from incompletely treated AVMs.…”
Section: Endovascular Embolization Of Avmsmentioning
confidence: 99%
“…Embolization prior to stereotactic radiosurgery has been performed as a way of decreasing the size of the nidus and thus the requisite radiation dose. [ 19 23 ] However, the published outcomes regarding this treatment protocol have been mixed. [ 3 6 15 38 39 ] Although the lower radiation dose decreases the risk to the surrounding normal tissue, several studies have reported a lower rate of obliteration following such a regimen without any decrease in the risk of hemorrhage during the latency period.…”
Section: Endovascular Embolization Of Avmsmentioning
confidence: 99%
“…When combined with radiosurgery, the target of embolization is often the periphery of the AVM to reduce the size and therefore the total radiation dose required. 61,62 Clinically significant complications have been reported to occur in $ 6.5% cases. 63…”
Section: Endovascular Treatmentmentioning
confidence: 99%